Metodik khusus pengajaran agama Islam - METODIK... (Direktorat Jenderal Pembinaan Kelembagaan Agama Islam, 1985)
ast c.1/ast c.2/ast c.3/oen, c.4/ast c.5-10/ir,c.11-14/en, c.15-17/ws.c.18-20/stock6=c.21